(untitled) (Medical Forum Monthly, 2021)
Objective: To compare the long term effects of Mulligan Mobilization with Movement versus Macquarie Injury Management Group on pain and function of knee osteoarthritis. Study Design: Randomized Controlled Trial study Place and Duration of Study: This study was conducted at the Revival Physiotherapy Center, Lahore in last 06 months. Materials and Methods: Through non-probability convenient sampling technique 26 diagnosed patients with osteoarthritis were included in the study. Subjects were randomly divided into two groups by using flip coin method. Patients in Group 1 received MIMG with conventional physical therapy and in Group 2 received MWM with conventional physical therapy. Visual analogue Scale, Non modified WOMAC were used as outcome measuring tools. Readings were taken pretreatment ad at the end of 6th week. Statistical analysis was done by SPSS 21.0. Results: There were statistically significant difference in results of VAS in between group analysis. Pain decreased to greater extent in post treatment of MMG with routine physical therapy group with mean value 8.89±2.37 as compared to 7.16±1.17 in MWM with routine physical therapy group. WOMAC Score increased to greater extent in post treatment of MIMG with routine physical therapy group with mean value 59.78±13.59 as compared to MWM with routine physical therapy 71.89±12.40. VAS score increased to greater extent in post treatment of mobilization with movement and with routine physical therapy group with mean value 17.84±3.71 as compared to routine physical therapy group 18.00±4.16. Conclusion: It concluded that Macquarie Injury Management Group has statistically significant results as compared to Mulligan Mobilization with Movement on pain and function of knee osteoarthritis.